Implementación de un túnel de termo encogido para embalar envases de yogurt de la microempresa de lácteos el excelente ubicada en la parroquia de Belisario Quevedo, cantón Latacunga en el año 2016 - Guagchinga Santo, Cristian Geovanny (2016)
This research work of Electromechanical Engineering Major is aimed at solving the problem of the packaging process in the Dairy Microenterprise El Excelente. All dairy industry meets the basic processes for the production of yogurt, and one of them is the packaging of the final product; through observation it could be identified that the aforementioned processing industry does not have the equipment for packing. Therefore, the main aim of this work is to implement the heat tunnel which will allow pack six or twelve units of 500 and 120 grams respectively. This work is to improve the protection, to keep the presentation, to optimize the order of the product in the holding chamber, and to facilitate the loading and unloading of product from the means of transport. The process is based on introducing containers wrapped by a thermoplastic polyethylene in a heat chamber at a constant temperature and speed, and thus comply with the shrunk heat phases; this exercise helps kill bacteria or microorganisms to obtain a clean product.